Cash transfers and fertility: Evidence from Poland’s Family 500+ Policy - Anna Bokun (Demographic Research)
BACKGROUND: To increase the lowest fertility rate in the European Union in 2015, combat poverty, and invest in children’s human capital, the Polish government launched a pronatalist cash transfer program in 2016. OBJECTIVE: What are the short-term fertility effects of the Family 500+ cash transfer? Which groups of women responded to the cash transfer? METHODS: Using the Polish Household Budget Survey (2010–2018), I estimate linear probability regression models to identify the effect of the cash transfer on the probability of a birth as a function of a woman’s cash transfer eligibility, including heterogeneous effects by age, income, and education. RESULTS: In the short term, the cash transfer is associated with an increased annual probability of overall births by 1.5 percentage points. Heterogeneity analyses reveal the cash transfer is associated with increased fertility for women aged 31–40 (0.7 to 1.8 percentage points), in contrast to decreased fertility for women aged 21–30 (2.2 to 2.6 percentage points) and women with higher household incomes (1 percentage point). CONCLUSIONS: This analysis provides mixed evidence on the short-term efficacy of the cash transfer on fertility. Some demographic groups are more sensitive to the additional income, suggesting that the economic and social barriers to fertility are not equally distributed in the Polish population. CONTRIBUTION: Descriptive analyses of changing short-term fertility can facilitate timely adjustments to policies, identify emerging trends that may signal long-term patterns, and inform resource allocation.